Nutrition, breeding and biotechnology of leguminous root crops for food security: Yam bean, African yam bean and Winged bean - Gomathi , S; Murugesan, P; Sujatha, K; Daniel, B A; Ashwini, A; Venudevan, B; Alex, A V; Perinba, S C; Thangamuniyandi, M (Plant Science Today, 2025)
Yam bean (Pachyrhizus spp.), African yam bean (Sphenostylis stenocarpa) and winged bean (Psophocarpus tetragonolobus) are protein- and carbohydrate-rich leguminous root crops with significant potential for food security and industrial applications. Yam bean (P. erosus) has potential to yield storage root between 120 - 145 t/ha, with a starch content of 45-55 %, while its seeds contained 29.2 % - 32.1 % protein and 14.09 % - 18.91 % crude fat, making it a nutritionally valuable leguminous tuber crop​. Advances in its breeding included SSR markers for diversity assessment, rotenone-free cultivars and interspecific hybridization. African yam bean is cultivated across West and Central Africa, with storage root yields reaching up to 80 t/ha and seed yields ranging from 0.4 to 2.8 t/ha, while its tubers contained 16 % protein and 68 % carbohydrates and seeds provided 37 % protein and 64 % carbohydrates. Recent genetic improvements included early-maturing varieties (120 - 150 days), SNP markers for yield selection and enhanced disease resistance against anthracnose and rust. Winged bean produced tuber yields of 15.5 t/ha and seed yields up to 4.0 t/ha, with seeds containing 28 % - 45 % protein and 14 % - 20.4 % fat, while tubers offer 12.26 % - 19.07 % protein and served as a carbohydrate-rich food source. Genetic advancements in marker-assisted selection (MAS), QTL mapping (qPL1, qSS2, qFC3) and mutation breeding (gamma irradiation 100 - 400 Gy) had improved productivity. Additionally, the tissue culture protocol for winged bean seeds was optimized using MS media supplemented with 2.0 mg/L BAP and 0.5 mg/L NAA, resulting in 92 % shoot regeneration. Future research is recommended to focus on genome editing, polyploid breeding, post-harvest optimization and functional food applications to enhance crop utilization and sustainability.